Strategi Pengembangan Agrowisata Taman Eden 100 di Tengah Pandemi Covid-19 di Desa Sionggang Utara Kecamatan Lumban Julu Kabupaten Toba Provinsi Sumatera Utara - PASARIBU, JOSEPA; PITANA, I GDE; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Strategy for the Development Eden Park 100 Agrotourism in The Midst Of The Covid-19 Pandemic in North Sionggang Village, Lumban Julu District, Toba County North Sumatra Eden Park 100 is an open space agrotourism in North Sionggang Village, North Sumatra. The results showed that the I-E matrix analysis was classified into cell V, where agrotourism was obliged to develop its tourist attraction while encouraging market expansion. The SWOT analysis produces four alternative strategies, namely: (a) SO Strategy (market expansion, collaboration with government and entrepreneurs, improving health protocols), (b) ST Strategy (reinforcing the concept of environmentally friendly agro-tourism, optimizing agricultural processing), (c) WO Strategy (implementing diversification of Learning Farm, improving the quality of human resources management, and improve the digital ability to expand the market share of Andaliman, (d) WT Strategy (improving productivity of Andaliman and developing agricultural tourism attractions). Priority analysis of agro-tourism strategy sequentially starts with market expansion by highlighting the attractiveness of agricultural activities.